DEVELOPMENT TRENDS OF DIGITAL ECONOMY AND FINANCIAL INCLUSION IN UZBEKISTAN’S BANKING SYSTEM (American Journal of Business Management, Economics and Banking, 2025)
The article analyzes the development trends of digital economy and financial inclusion in Uzbekistan’s banking system from 2020 to 2025. Using statistical, comparative, and SWOD analysis, the study demonstrates the growth of digital services, mobile payments, online banking, and financial literacy programs. The social impact of digital finance, including access to banking services for rural populations, women, and youth, is also discussed. The article provides recommendations for adopting Reg Tech and AI technologies, improving financial literacy, and enhancing cybersecurity.